2012
DOI: 10.1016/j.bbadis.2011.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies in primary Sjögren's syndrome patients induce internalization of muscarinic type 3 receptors

Abstract: pSS IgG induces internalization of M3R partly through a clathrin-mediated pathway. The results suggest M3R internalization as a potential mechanism to explain the exocrinopathy seen in pSS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…These results suggest that IgG from SS patients induce internalization of M 3 mAChR partly through a clathrinmediated pathway. They also provide support to the notion that antimAChR M 3 antibodies cause salivary dysfunction in patients with SS via both a reduction of calcium influx and the down-regulation of M 3 mAChR molecules on epithelial cells of salivary glands [76].…”
Section: Action Of Anti-muscarinic Acetylcholine Receptors Antibodiesmentioning
confidence: 57%
“…These results suggest that IgG from SS patients induce internalization of M 3 mAChR partly through a clathrinmediated pathway. They also provide support to the notion that antimAChR M 3 antibodies cause salivary dysfunction in patients with SS via both a reduction of calcium influx and the down-regulation of M 3 mAChR molecules on epithelial cells of salivary glands [76].…”
Section: Action Of Anti-muscarinic Acetylcholine Receptors Antibodiesmentioning
confidence: 57%
“…[16] demonstrated that carbacholinduced calcium mobilization was inhibited by long-term incubation of the cells for 12 h with anti-M3R autoantibodies. The mechanism underlying the chronic inhibitory effect of anti-M3R autoantibodies shown in HSG cells was further investigated in primary cultured hSMG epithelial cells [13]. In hSMG cells, M3R was internalized via clathrin-mediated endocytosis by incubation with pSS IgG for longer than 30 min (Figure 1).…”
Section: Inhibition Of Muscarinic Receptor Function In Various Tissuementioning
confidence: 99%
“…These findings strongly suggest that anti-M3R autoantibodies have multifaceted effects, possibly not only through direct binding of anti-M3R autoantibodies to M3R but also by affecting other molecules involved in salivary secretion. [13]. Prior to pSS IgG incubation, M3R was located predominantly at the cell membrane, while clathrin was in the cytosol.…”
Section: Inhibition Of Muscarinic Receptor Function In Various Tissuementioning
confidence: 99%
See 2 more Smart Citations